CBSE BOARD X, asked by saniyateresa, 11 months ago

On dividing x^3- 3x^2 + x + 2 by a polynomial g(x), the quotient and remainder were x- 2 and - 2x+4 respectively.Find g(x)?

Answers

Answered by TakenName
17

x^3-3x^2+x+2 is the dividend.

Let the dividend be P(x), P(x) means; polynomial for x.

Then we have P(x)=g(x)(x-2)-2x+4.

By moving the side of the remainder, we get g(x)(x-2)=P(x)+2x-4.

We can rewrite P(x)=x^3-3x^2+x+2.

Now we have g(x)(x-2)=x^3-3x^2+3x-2.

By dividing both sides by x-2, we get x²-x+1. Therefore g(x)=x²-x+1.

I hope this helped, please post more questions on brainly.com.

Similar questions